Enzymatic enrichment of n-3 polyunsaturated fatty acid glycerides by selective hydrolysis. (1st June 2021) - Yang, Zhuangzhuang; Jin, Wenhua; Cheng, Xinyi; Dong, Zhe; Chang, Ming; Wang, Xiaosan
Highlights: n-3 PUFA glycerides were enzymatically enriched by selective hydrolysis. Lipase AY "Amano" 400SD showed remarkably hydrolytic discrimination against PUFA. SFAs and MUFAs were released from triglycerides to obtain PUFA-enriched glycerides. Addition of Ca 2+ to the system led to the decrease of reaction time from 10 to 4 h. PUFA content in algal oil after selective hydrolysis was up to 89.9% Abstract: Most natural oils are low in n-3 polyunsaturated fatty acids (n-3 PUFAs) content, which limits their application in health products. In this study, n-3 PUFAs in glyceride form were selectively enriched by lipase-mediated hydrolysis of n-3 PUFA-containing oils. First, commercial lipases were screened, and the lipase AY "Amano" 400SD from Candida cylindracea was the best choice in producing n-3 PUFA glycerides from tuna oil. Subsequently, the hydrolysis conditions were optimized. Under the optimal conditions, the highest n-3 PUFA content in the glyceride fraction was found to be 57.7% after enzymatic hydrolysis. Addition of Ca 2+ to the system significantly shortened the reaction time from 10 to 4 h. When algal oil was used as substrate, total PUFA contents in the glyceride fraction were 89.9%. This study provides an efficient enzymatic process to produce n-3 PUFA-enriched glyceride concentrates and demonstrates that AY "Amano" 400SD can effectively discriminate against n-3 PUFAs during hydrolysis.